The Effect of Student’s Motivation on Academic Achievement - Puput Iswandyah Raysharie; Luluk Tri Harinie; Nathaly Inglesia; Vita Vita; Santi Wati; Benedikta Sianipar; Ongki Ongki; Rihan Pasha; Muhammad Abdurrahman; Kemas Ary Fadilla; Febriana Putri (FKIP, Universitas Palangka Raya, 2023)
This quantitative study aims to investigate how intrinsic motivation affects students' performance in the Management degree at FEB Palangka Raya University. Purposive sampling was utilized to choose 123 students from the class of 2022 to participate in a survey. Participants' desire to learn was rated on a scale of 1–100 using the questionnaire, and their first-semester academic performance was evaluated using their individual version (IP) grade point average. EViews 12 was used to do the statistical analysis of the data. Students' grades (Y) were shown to be highly impacted by their level of learning motivation (X). The results of the statistical analysis, conducted using EViews 12, showed that there is a strong correlation between students' level of intrinsic motivation and their academic performance. Specifically, this study found that students who have higher levels of intrinsic motivation tend to have better academic performance than those who have lower levels of intrinsic motivation.